EFFICACY OF INTRATHECAL CHLOROPROCAINE AND BUPIVACAINE ON CLINICAL OUTCOMES IN PATIENTS UNDERGOING DAY-CASE SURGERY: A DESCRIPTIVE STUDY - Haj Hamad, Raheeq (An-Najah National University, 2025)
Background: Day-case procedures require anaesthetics with rapid onset, effective anesthesia, prompt recovery, and minimal complications. Bupivacaine provides extended analgesia but causes delayed recovery and potential hemodynamic instability. Chloroprocaine offers a swift onset and recovery; however, its use in outpatient surgery in Palestine remains inadequately investigated. Aim: To evaluate the efficacy and safety of intrathecal chloroprocaine compared with bupivacaine in patients undergoing outpatient (day-case) surgery by assessing key clinical outcomes. Methods: A descriptive comparative cross sectional study was conducted at Al Itihad Hospital in Nablus, Palestine, from March to June 2025. One hundred adult patients (ages 18-65) undergoing elective outpatient procedures under spinal anesthesia were randomized to receive either intrathecal chloroprocaine (Group A) or intrathecal bupivacaine (Group B). Primary outcomes measured were block properties and motor/sensory regression times. Secondary outcomes included hemodynamic stability, postoperative analgesia requirements, ambulation time, and complications. Data were analyzed using SPSS version 21, with p < 0.05 considered significant. Results: Chloroprocaine demonstrated faster sensory (3.12 ± 0.56 min) and motor block onset (4.92 ± 0.63 min) compared to bupivacaine (4.26 ± 0.53 min and 5.68 ± 0.86 min, respectively; p < 0.01). The chloroprocaine group experienced shorter block duration. This has lead to quicker ambulation and discharge. More chloroprocaine patients required postoperative analgesics (66% vs. 38%; p = 0.003). Hemodynamic measures including hypotension, bradycardia, and hypertension showed no significant differences between groups. No serious complications occurred. Conclusion: Both chloroprocaine and bupivacaine are safe and effective for spinal anesthesia in outpatient procedures. Chloroprocaine offers rapid onset, reduced recovery time, and expedited discharge but requires more postoperative analgesia.
فعالية الكلوروبروكائين والبوبيفاكائين داخل الجافية على النتائج السريرية لدى المرضى الذين يخضعون لجراحة اليوم الواحد: دراسة وصفية